A systematic analysis of nucleosome core particle and nucleosome-nucleosome stacking structure - Korolev, Nikolay (2018)
Chromatin condensation is driven by the energetically favourable interaction between nucleosome core particles (NCPs). The close NCP-NCP contact, stacking, is a primary structural element of all condensed states of chromatin in vitro and in vivo. However, the molecular structure of stacked nucleosomes as well as the nature of the interactions involved in its formation have not yet been systematically studied. Here we undertake an investigation of both the structural and physico-chemical features of NCP structure and the NCP-NCP stacking. We introduce an “NCP-centred” set of parameters (NCP-NCP distance, shift, rise, tilt, and others) that allows numerical characterisation of the mutual positions of the NCPs in the stacking and in any other structures formed by the NCP. NCP stacking in more than 140 published NCP crystal structures were analysed. In addition, coarse grained (CG) MD simulations modelling NCP condensation was carried out. The CG model takes into account details of the nucleosome structure and adequately describes the long range electrostatic forces as well as excluded volume effects acting in chromatin. The CG simulations showed good agreement with experimental data and revealed the importance of the H2A and H4 N-terminal tail bridging and screening as well as tail-tail correlations in the stacked nucleosomes.